2014
DOI: 10.1093/cid/ciu446
|View full text |Cite
|
Sign up to set email alerts
|

Added Benefit of Nucleic Acid Amplification Testing for the Diagnosis of Trichomonas vaginalis Among Men and Women Attending a Sexually Transmitted Diseases Clinic

Abstract: TV prevalence among men and women was high in this study, suggesting that both groups should be routinely screened, including those aged >40 years. Improved detection of TV by routine implementation of NAATs should result in better control of this common, treatable STI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
1
36
2
Order By: Relevance
“…A recent study from the Cleveland Clinic in September 2016 [15] showed a detection rate of Trichomonas in urinary cytology as only 0.1% (73 cases of 60,000 specimens) over a 30-year period. This contrasts with reported rates of up to 20% trichomoniasis in patients attending sexually transmitted diseases clinics [2,6] . Also, male partners of women with trichomoniasis were infected in surprising 72%, most of them being asymptomatic [11] .…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…A recent study from the Cleveland Clinic in September 2016 [15] showed a detection rate of Trichomonas in urinary cytology as only 0.1% (73 cases of 60,000 specimens) over a 30-year period. This contrasts with reported rates of up to 20% trichomoniasis in patients attending sexually transmitted diseases clinics [2,6] . Also, male partners of women with trichomoniasis were infected in surprising 72%, most of them being asymptomatic [11] .…”
Section: Discussioncontrasting
confidence: 79%
“…With newer methods such as nucleic acid amplification [5,6] , the prevalence of Trichomonas and Chlamydia in men attending a sexually transmitted diseases clinic were shown to be as high as 17 and 19%, respectively [2] . In men with non-gonococcal urethritis, 19.9% were infected with Trichomonas [6] . Equally significant is the detection of HPV in human semen specimen in 14.9% [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of the 24 missed STI diagnoses were due to T. vaginalis. T. vaginalis is the most common nonviral STI and is often missed by non-NAAT methods (4,15). In a recent study including women Ն16 years of age attending a sexually transmitted disease clinic utilizing NAAT methods (14), the overall prevalence of T. vaginalis was 27%, with the highest prevalence (34%) in women Ͼ40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to trichomoniasis in female subjects, the association between T . vaginalis infection and older age in male subjects is not fully understood [35, 36]. Previous surveillances in the United States indicated that the highest prevalence of T .…”
Section: Discussionmentioning
confidence: 99%